Pembubaran Organisasi Kemasyarakatan dalam Perspektif Hak Kebebasan Berserikat Berdasarkan Konstitusi Negara Republik Indonesia - M. Asfa Firosa (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2019)
This article is intended to address the problem of the dissolution of social organizations as stated in social organizations law viewed from the principles of state law, democracy and human rights. The method used is normative juridical. The approach used is the statutory approach and conceptual approach. This article concludes that the mechanism for dissolution of civil society organizations has become more concise by not passing through the courts because of the inclusion of the contrarius actus principle. This is not in accordance with the principles of state law, democracy and human rights. Social Organization as an important instrument in democracy and a form of freedom of association, the dissolution has to be decided through a due process mechanism of law by an independent court. This legal process becomes very important because the dissolution carried out by an executive institution unilaterally will lead to arbitrariness.